PENGARUH UMUR, BIAYA TRANSFER DAN BIAYA GAJI TERHADAP MARKET VALUE PEMAIN SEPAKBOLA PROFESIONAL (Studi Pada Klub Sepakbola Eropa) - B51111097, Indra Situmorang (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Market Value is the monetary value of a football player who is reported in the financial statements of a football club as a professional accounting practice of human resources in the football industry. This study aims to demonstrate the influence of age, Transfer Fees and Salary Cost to Market Value on European football clubs in the 2014/2015 season. Population and sample of this research is a soccer player of four professional soccer clubs in Europe that issued the club's financial statements to the public. The total sample of 60 players are determined through purposive sampling that is the player most often played for the club throughout the season 2014/2015. Data analysis was performed with the classical assumption that the normality test, multicollinearity, and autocorrelation test heterocedasticity then hypothesis testing was done using a multiple linear regression method. The results of this study indicate that the age factor of a significant negative effect on the market value of soccer player. While the cost factor transfers and salaries positive effect on the market value of a football player. The conclusion from this study is that age, transfer fee and salary costs can be used to estimate the price of a professional soccer player. Â  Keywords : Human Resource Accounting, Market Value, Age, Transfer Fees, Expenses Salaries, Football